INTENSITY AND CONTRAST OF A HOLOGRAPHIC IMAGE - MALACARA HERNANDEZ, D (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1965)
In this paper the intensities of holographic images are described by means of graphs obtained using a digital computer. The film characteristic curve is either assumed to be linear of that the maximum and minimum exposures are both on the straight portion
BOL OBS TONAN TACUB
Keywords: INTENSITY, CONTRAST, HOLOGRAPHIC IMAGE; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; HOLOGRAFIA